Capacity Building in Nurturing Care in Serbia. (13th November 2019) - Jankovic, S Mladenovic; Matijevic, D; Tamburkovski, G; Grujicic, A; Markovic, M
Abstract: Background: Training program for home visitors on early child development was developed and implemented within UNICEF supported projects involving 25 primary health centers. Training content was notably based on resource modules "Supporting Families for Nurturing Care", adapted according to the local context. Health professionals are seen as the critical actors to support development of young children and their families. Family-centered approach that addresses social as well as medical dimensions of problems became priority in their practice with a special focus on working with children from socially deprived settings and children with disabilities. Objectives: The main objective was to improve knowledge and practice of home visitors on early child development based on most recent scientific evidence. Broad spectrum of topics was covered including engaging fathers, early detection of postpartum depression, attachment, developmental monitoring, age-appropriate play, home safety, stigma and discrimination. Training were organized as interactive face to face sessions and online courses and attendees were actively engaged in reflection. Comprehensive check list with various assessment instruments was developed to provide guidance to home visitors in implementation of gained skills. Results: Increase in knowledge of 150 home visitors was between 57.6% and 82.9%. Enhanced knowledge and skills have been applied in 14912 families of which socially deprived was 34.5% during 2-year period of implementation. Parent-child interactions, assessed by visiting nurses, were improved by 32.6%, responsive feeding practices by 27.4%, while age-appropriate play by 34.4% after interventions during home visits. Conclusions: Well-developed monitoring system was crucial for implementation of gained knowledge and skills in practice of home visitors. Key messages: Home visitors were empowered to take a strengths-based approach in their work with families. Developed tools facilitated prioritization of most vulnerable families and tailoring support according to needs.